Filtration Performance of Woven Geotextiles With Wastewater Treatment Sludge. Issue 1 (1st January 2002) - Aydilek, A.H.; Edil, T.B.
Abstract : Capping of contaminated soft sediments and sludges for in situ containment provides an efficient remediation alternative. Capping design typically involves the use of geosynthetics for multiple functions, e.g., reinforcement, separation, and filtration. Filtration performance becomes a decisive factor for proper long-term performance of a cap. Because of multiple functions required, woven geotextiles are often the choice geosynthetic in such applications. A research program concerning the filtration behavior of contaminated wastewater treatment sludges was conducted. The laboratory portion of the program included a series of filtration tests with different woven geotextiles. Filtration performance of the sludge-woven geotextile systems was also observed in field test cells. Geotextile samples were exhumed from the cells after exposure and analyzed in the laboratory. The results indicate that the sludges can be filtered using woven geotextiles and the selection of a proper filter can be made on the basis of geotextile pore structure parameters, i.e. percent open area and pore opening size distribution. The standard gradient ratio test did not always reflect the filtration performance and, therefore, other clogging ratios need to be considered. A commonly used geotextile pore opening size-to-soil particle ratio in the existing filter criteria, O95 / D85, did not predict the filtration behavior displayed by the sludge; however, another ratio, O50 / D50, showed general correlation to clogging and retention.